(untitled) (Portuguese Journal of Family Medicine and General Practice, 2025)
Introduction: Clinical ethics involves identifying, analyzing, and resolving ethical problems that arise in healthcare practice. This study aimed to describe how health professionals identify and manage clinical ethics issues and to identify which tools and support structures they consider useful. Methods: A cross-sectional, observational study was conducted among health professionals working in primary care in the Administração Regional de Saúde de Lisboa e Vale do Tejo (ARSLVT). A one-stage, stratified, simple cluster random sampling method was used to select a total of 400 professionals. A self-administered questionnaire, previously applied in four European countries, was adapted and pilot-tested for this context. Results: A total of 204 questionnaires were collected. Ninety-six percent of participants reported experience with at least one of seven types of ethical problems described. The most frequently identified issues were caring for adults whose decision-making capacity regarding their health was unknown or impaired (94%), and situations where resource management required professionals to make choices different from those they desired (81%). Only 16% of professionals had used any of the described ethical support resources. The most valued resources for resolving ethical conflicts were those providing help in clarifying ethical issues for themselves and other professionals involved (42%). Conclusion: Ethical problems are an inherent part of the complexity of healthcare, highlighting the need for adequate ethical support in decision-making. However, the low use of such resources among professionals stands out as a key finding. This should be considered when designing organizational models for ethical decision support.